Medicinal plants: bioactive compounds, biological activities, combating multidrug-resistant microorganisms, and human health benefits - a comprehensive review - El-Saadony, Mohamed T.; Saad, Ahmed M.; Mohammed, Dina Mostafa; Korma, Sameh A.; Alshahrani, Mohammad Y.; Ahmed, Ahmed Ezzat; Ibrahim, Essam H.; Salem, Heba M.; Alkafaas, Samar Sami; Saif, Abdullah M.; Elkafas, Sara Samy; Fahmy, Mohamed A.; et al. (Frontiers in Immunology, 2025)
In recent years, medicinal plants have gained significant attention in modern medicine due to their accessibility, affordability, widespread acceptance, and safety, making herbal remedies highly valued globally. Consequently, ensuring medicinal plants’ quality, efficacy, and safety has become a critical concern for developed and developing nations. The emergence of multidrug-resistant microorganisms poses a serious global health threat, particularly in low-income regions, despite significant advancements in antimicrobial drugs and medical research over the past century. The rapid spread of these multidrug-resistant infections is primarily attributed to improper prescriptions, overuse, and unregulated access to antibiotics. Addressing these challenges, the standardization of plant-derived pharmaceuticals could pave the way for a transformative era in healthcare. Preserving and leveraging the historical knowledge of medicinal plants is essential before such valuable information is lost. Recently, there has been growing interest among natural and pharmaceutical scientists in exploring medicinal plants as potential sources of antimicrobial agents. This current review aims to identify the most common pathogens threatening human health, analyze the factors contributing to the rise of drug-resistant microorganisms, and evaluate the widespread use of medicinal plants across various countries as alternative antibiotics, highlighting their unique mechanisms of antimicrobial resistance.